Anti-cyclooxygenase, anti-glycation, and anti-skin aging effect of Dendrobium officinale flowers’ aqueous extract and its phytochemical validation in aging - Zhou, Huiji; Zhou, Luxian; Li, Bo; Yue, Rongcai (Frontiers in Immunology, 2023)
Introduction Dendrobium officinale Kimura et Migo (D. officinale) , widely called as “life-saving immortal grass” by Chinese folk, is a scarce and endangered species. The edible stems of D. officinale have been extensively studied for active chemical components and various bioactivities. However, few studies have reported the well-being beneficial effects of D. officinale flowers (DOF). Therefore, the present study aimed to investigate the in vitro biological potency of its aqueous extract and screen its active components. Methods Antioxidant tests, including 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), the ferric reducing ability of plasma (FRAP), and intracellular reactive oxygen species (ROS) level analyses in primary human epidermal keratinocytes, anti-cyclooxygenase2 (COX-2) assay, anti-glycation assay (both fluorescent AGEs formation in a BSA fructose/glucose system and glycation cell assay), and anti-aging assay (quantification of collagen types I and III, and SA-β-gal staining assay) were conducted to determine the potential biological effects of DOF extracts and its major compounds. Ultra-performance liquid chromatography-electrospray ionisation-quadrupole-time-of-flight-mass spectrometry (UPLC-ESI-QTOF-MS/MS) was performed to investigate the composition of DOF extracts. Online antioxidant post-column bioassay tests were applied to rapidly screen major antioxidants in DOF extracts. Results and discussion The aqueous extract of D. officinale flowers was found to have potential antioxidant capacity, anti-cyclooxygenase2 (COX-2) effect, anti-glycation potency, and anti-aging effects. A total of 34 compounds were identified using UPLC-ESI-QTOF-MS/MS. Online ABTS radical analysis demonstrated that 1-O-caffeoyl-β-D-glucoside, vicenin-2, luteolin-6-C-β-D-xyloside-8-C-β--D-glucoside, quercetin-3-O-sophoroside, rutin, isoquercitrin, and quercetin 3-O-(6″-O-malonyl)-β-D-glucoside are the major potential antioxidants. In addition, all selected 16 compounds exerted significant ABTS radical scavenging ability and effective AGE suppressive activities. However, only certain compounds, such as rutin and isoquercitrin, displayed selective and significant antioxidant abilities, as shown by DPPH and FRAP, as well as potent COX-2 inhibitory capacity, whereas the remaining compounds displayed relatively weak or no effects. This indicates that specific components contributed to different functionalities. Our findings justified that DOF and its active compound targeted related enzymes and highlighted their potential application in anti-aging.